Genetic Polymorphism of Glutathione S-transferase and Cervical Cancer Susceptibility in Northeastern Thailand - Settheetham-Ishida, wannapa; Wongpratate, Mayuree; Phuthong, Sophida; Natphopsuk, Sitakan; Ishida, Takafumi (Asian Pacific Journal of Cancer Biology, 2020)
Background: Exposure to certain carcinogens together with host genetic predisposition likely has an influence on cervical carcinogenesis. Objective: Our aim was to evaluate synergistic effects of glutathione S-transferase (GST) polymorphisms and risk behaviors (i.e., smoking and contraceptive use) on squamous cell cervical cancer (SCCA) development in northeastern Thailand. Methods: Subjects were 198 (SCCA) patients and 198 age-matched healthy controls. Multiplex PCR and PCR-RFLP were used to determine GSTT1 and GSTA1 gene polymorphism, respectively. Results: Interaction between the four polymorphic loci of GSTs (GSTM1, GSTT1, GSTP1 and GSTA1) and increased risk for cervical cancer was not observed. The three genotypes of GSTM1 consistently showed significant risks of smoking with a lower OR for the Null individuals (1.741) at around one -fourth of wild type homozygous individuals (8.000). The effects of GST polymorphisms on cervical cancer risk under the use of hormonal contraceptives apparently did not occur. Conclusions: The predisposition of smoking risk is related to the GST genotype. It is suggested that knowing one’s own genotype data will contribute to the prevention of SCCA by controlling risk habits.